A comparative study on eye tracking existing techniques - Bilal, Sara Mohammed Osman Saleh; Bahri, Nurshafiqah; Khalifa, Othman Omran (2014)
An eye tracker is a device for measuring eye positions and eye movement. During the past decades, various approaches have been presented for eye tracking to help disabled people in various tasks such as communication, writing emails, drawing, besides other applications such as cognitive studies and commercial eye trackers. The eye tracking devices and the algorithms that track the gaze still need enhancement. Many critical problems arise from the fact that the eye tracker system does not retain its accuracy for a long period. In this paper, a comprehensive study based on the factors such as camera calibration , eye blinking and head movement that affect the existing eye trackers performance will be highlighted. This study can be a reference for any Human to computer Interaction (HCI) application that requires eye tracking with high visual quality and cheap price.